From fascism to populism in history - Finchelstein, Federico, 1975- (University of California press, 2017)
Fascism and populism are at the center of political discussions today. Although they are often conflated, they represent alternative global trajectories. This book represents a historian's inquiry into how and why fascism became linked with populism in history. Stressing the significant differences between populism as form of democracy and fascism as a form of dictatorship, From Fascism to Populism in History rethinks the conceptual and historical experiences of fascism and populism by assessing their elective ideological affinities and substantial political differences in history and theory